PENGARUH AKUNTANSI FORENSIK, SKEPTISME PROFESIONAL DAN PENGALAMAN AUDIT TERHADAP DETEKSI FRAUD - Rahmawati, Annisa; Simorangkir, Panubut; Ginting, Rudi (Jurnal Akunida, 2021)
This study aims to analyze the effect of forensic accounting, auditor professional skepticism, and audit experience on fraud detection. Data was collected by distributing questionnaires to respondents. The population in this study are auditors who work in a public accounting firm (KAP) in Jakarta, with a sample of 100 auditors. The sampling technique used is purposive sampling with the criteria of auditors who are still actively working at KAP in DKI Jakarta and have at least 6 months of experience working at KAP. Data analysis method used multiple linear regression analysis. Partially, the results showed that forensic accounting and audit experience had a significant positive effect on fraud detection, while professional auditor skepticism had no significant effect on fraud detection.